2018
DOI: 10.1071/ah16222
|View full text |Cite
|
Sign up to set email alerts
|

Do patients discharged from advanced practice physiotherapy-led clinics re-present to specialist medical services?

Abstract: Objective. The aim of the present study was to determine the rates of re-referral to specialist out-patient clinics for patients previously managed and discharged from an advanced practice physiotherapy-led service in three metropolitan hospitals.Methods. A retrospective audit was undertaken of 462 patient cases with non-urgent musculoskeletal conditions discharged between 1 April 2014 and 30 March 2015 from three metropolitan hospitals. These patients had been discharged from the physiotherapy-led service wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…The findings of this service evaluation show that the majority of patients (75%) directed to the MAC were independently managed by the CSPs without review by the rheumatology consultant or team. This is comparable to the findings of similar orthopedic service evaluations , which have reported that 50%‐92% of patients seen in physiotherapist‐led triage services were managed without referral to orthopedic clinics.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings of this service evaluation show that the majority of patients (75%) directed to the MAC were independently managed by the CSPs without review by the rheumatology consultant or team. This is comparable to the findings of similar orthopedic service evaluations , which have reported that 50%‐92% of patients seen in physiotherapist‐led triage services were managed without referral to orthopedic clinics.…”
Section: Discussionsupporting
confidence: 86%
“…A substantial number of trials, observational studies, and service evaluations of physiotherapist‐led musculoskeletal triage services in primary and secondary care settings have found that suitably trained CSPs can independently and appropriately manage a significant proportion (50%‐92%) of patients within physiotherapist‐led musculoskeletal triage clinics . A systematic review of extended‐scope physiotherapy practice in patients with musculoskeletal disorders suggests that the quality of care is at least equivalent to that of physician‐led care with respect to diagnostic accuracy, clinical effectiveness, use of health care resources, and patient satisfaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The international physiotherapy literature provides many examples of ACPs delivering new models of care, particularly in musculoskeletal services, and across different settings, including emergency, primary and secondary care. [20][21][22][23][24][25][26][27] Many of these examples involved the physiotherapy ACPs assessing and treating patients for musculoskeletal conditions, instead of medical practitioners, both in routine clinics and emergency care. These models consistently evaluate well, providing not only an equivalent quality but also additional benefits, such as increased accessibility and wider range of strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Within health services with existing AMP services, experienced and qualified musculoskeletal physiotherapists have a pathway to achieve full advanced practice competency, supported by a competency‐based training and assessment framework leading to credentialing (Department of Health, ). This has resulted in the formation of a capable workforce which has further potential to improve patient outcomes and the efficiency and cost‐effectiveness of service delivery (Chang, Gavaghan, O'Leary, McBride, & Raymer, ).…”
Section: Introductionmentioning
confidence: 99%